Model Hubungan Pertukaran Waktu dan Biaya pada Rangka Plafon di Kabupaten Aceh Barat Daya - rahmi maulina rahayu; Fachrurrazi Fachrurrazi; Febriyanti Maulina (Journal of The Civil Engineering Student, 2020)
Competition in the construction services business cannot be avoided, this is certainly a challenge for service providers, especially contractors. The contractor must use the right competitive strategy so that the company can survive in the business field. One strategy that can be done is to accelerate the project. This study examines how much additional costs due to acceleration per day. This study aims to create a model of the exchange relationship between time and cost on the ceiling frame work in the Southwest Aceh District. The model was developed from questionnaire data and secondary data obtained through directors, managers, company estimators domiciled in Southwest Aceh District. The analysis used for the development of the model is regression analysis. The ceiling frame work model is c = 117,037,315,49 - 2,678,101.83d. The parameters of the exchange relationship model between time and cost on ceiling frame work are normal duration (Dn) 10 days, crash duration (Dc) 6 days, maximum acceleration that can be done 4 days (40% of normal duration) and additional costs per day Rp. 2727. 488 (2.93% of normal costs).